The impact of affirmative action in India and the United States: A systematic literature review - Simone Schotte; Tharcisio Leone; Rachel M. Gisselquist (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This paper provides a systematic review of quantitative literature investigating the success of affirmative action (AA) policies in addressing socio-economic inequalities between ethnic groups in education and employment. We focus on two of the most influential national experiences: caste-based AA in India and race-based AA in the United States. We find that AA has been successful in extending the opportunities available to target groups in both countries, with the Indian reservation policy showing stronger effects on the representation of minorities than non-quota measures in the US. Evidence on the impact of AA on the performance and actual achievements of target groups is more diverse. This is primarily due to mixed findings regarding the prevalence of academic mismatch among students admitted via AA, which has been investigated primarily in the US context. Evidence on the spillover effects of AA to non-target groups is scarce but points to negative replacement effects among over-represented groups.
Keywords: I38; J15; 330; affirmative action; systematic review; inequalities; India; United States